Integrating climate change adaption and development: Past trends and ways forward for Danish development cooperation - Mikkel Funder; Lily Salloum Lindegaard; Esbern Friis-Hansen; Marie Ladekjær Gravesen (Danish Institute for International Studies (DIIS), 2020)
Climate change has a severe impact on the livelihoods and economies of developing countries and will constrain achievement of the Sustainable Development Goals on virtually all fronts. While efforts to reduce emissions are obviously vital, it is equally critical that societies adapt to the already ongoing impact of climate change. Integrating climate change adaptation broadly into development cooperation is therefore a pressing issue and has never been more relevant. Discussion of the relationship between climate change adaptation and development and how to "mainstream" adaptation into development support is not new. However, uncertainty persists regarding the ways and extent to which adaptation should be addressed as part of broader development efforts. This new DIIS Report seeks to address the integration of adaptation and development, with a particular focus on Denmark's development cooperation. The report discusses the linkages between adaptation and development, examines the approaches of selected development actors, and discusses selected trends in Denmark's funding to climate change adaptation. The report concludes that despite challenges there are currently good opportunities and a growing momentum among key actors towards finally integrating adaptation and development. Denmark should take a global leading role in this by making climate action a main aim in development cooperation, and by adopting approaches that address climate change and development in an integrated manner from the outset of policy development and -programming.
Keywords: 300; Entwicklungshilfe; Dänisch; Klimapolitik; Nachhaltige Entwicklung; Entwicklungsländer; Dänemark